2008
DOI: 10.1074/jbc.m803351200
|View full text |Cite
|
Sign up to set email alerts
|

Arginines in the First Transmembrane Segment Promote Maturation of a P-glycoprotein Processing Mutant by Hydrogen Bond Interactions with Tyrosines in Transmembrane Segment 11

Abstract: A key goal is to correct defective folding of mutant ATP binding cassette (ABC) transporters, as they cause diseases such as cystic fibrosis. P-glycoprotein (ABCB1) is a useful model system because introduction of an arginine at position 65 of the first transmembrane (TM) segment could repair folding defects. To determine the mechanism of arginine rescue, we first tested the effects of introducing arginines at other positions in TM1 (residues 52-72) of a P-glycoprotein processing mutant (G251V) that is defecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…IH2 is in an intracellular loop between TM segments 4 and 5 that connects TMD1 to NBD2. IH2 appears to be particularly important because we showed that a cysteine introduced into IH2 (A266C) could be directly cross-linked to a cysteine in NBD2 (F1086C) but the mutant was inactive (21). By contrast, cysteine mutations at the equivalent sites at the fourth transmission interface (links IH4 in TMD2 to NBD1) (L443C(NBD1)/S909C(IH4) had no effect on activity (21).…”
Section: Atp-binding Cassette (Abc)mentioning
confidence: 91%
“…IH2 is in an intracellular loop between TM segments 4 and 5 that connects TMD1 to NBD2. IH2 appears to be particularly important because we showed that a cysteine introduced into IH2 (A266C) could be directly cross-linked to a cysteine in NBD2 (F1086C) but the mutant was inactive (21). By contrast, cysteine mutations at the equivalent sites at the fourth transmission interface (links IH4 in TMD2 to NBD1) (L443C(NBD1)/S909C(IH4) had no effect on activity (21).…”
Section: Atp-binding Cassette (Abc)mentioning
confidence: 91%
“…Better understanding of how Mdr transporters respond conformationally to dissimilar substrates in a transport-competent manner would add mechanistically important clues to how dissimilar compounds are actively exported by such transporters. For example, in a P-glycoprotein mutant that is defective in biogenesis, it has been reported that mutations in the binding site improve protein maturation and that this effect can also be achieved by substrates (27)(28)(29)(30)(31)(32). Thus, binding site modifications also have substrate-mimicking effects in this ATP-binding cassette Mdr transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Loo and Clarke performed numerous studies in order to define amino acids facing the membrane phase, thus interacting with the lipid environment. In these studies, a construct with the G251V mutation, causing protein instability and improper maturation (processing mutant), was used in combination with Arg mutations in transmembrane helices (Loo, Bartlett, & Clarke, 2008;Loo et al, 2009;Loo & Clarke, 2013). As a result, some "corrector" mutations rescued the processing mutant G251V by promoting its proper folding by Loo et al (2008).…”
Section: P0340mentioning
confidence: 99%
“…In these studies, a construct with the G251V mutation, causing protein instability and improper maturation (processing mutant), was used in combination with Arg mutations in transmembrane helices (Loo, Bartlett, & Clarke, 2008;Loo et al, 2009;Loo & Clarke, 2013). As a result, some "corrector" mutations rescued the processing mutant G251V by promoting its proper folding by Loo et al (2008). The authors hypothesized that when the inserted Arg faces the lipid interface, the rescue fails because of the intolerability of the positive charge in the hydrophobic environment (see Fig.…”
Section: P0340mentioning
confidence: 99%